Does sustainability practices, corporate governance and social responsibility affect risk and return of investments? - Milani, Bruno; Righi, Marcelo Brutti; Ceretta, Paulo Sérgio; Dias, Valéria da Veiga (Revista de Administração da UFSM, 2012)
This article aims to verify whether the investments in companies with better practices of Corporate Social Responsibility, Corporate Governance and Sustainability presents performance differences in relation to investments in companies that represent the market. To this end, we analyzed the series of daily returns of Ibovespa, IGC, IGCT, ISE and ITAG through GARCH model and mean differences tests. The results show that the conditional volatility of the differentiated practices indexes is significantly smaller than the Ibovespa volatility, although the correlation between the returns is very high. Besides that, the Sharpe Index (1966) of the better practices indexes shows that their return per unit of risk is significantly higher than Ibovespa’s. Thus, in general, it is possible to conclude that investments in different practices constitute a less risky and more profitable alternative to the investor.